Philippine agenda - Soho, Jessica; Clavio, Arnold; Enriquez, Mike; Tiangco, Mel; Morales, Vicky; Parungao, Monti (GMA Network, 2007)
This groundbreaking pre-election series combined the efforts of GMA Network's multi-awarded news and public affairs teams to present the country's biggest issues with the objective of calling viewers to action.